Pantoea agglomerans Infections in Children: Report of Two Cases. (21st January 2018) - Siwakoti, Shraddha; Sah, Rinku; Rajbhandari, Rupa Singh; Khanal, Basudha
Abstract : Introduction . Pantoea agglomerans, primarily an environmental and agricultural organism has been reported as both commensal and pathogen of humans. We present two case reports of P. agglomerans infections in children that involved the meninges and bloodstream. Case Presentations . A 6-month-old female baby, diagnosed as congenital hydrocephalus secondary to aqueduct stenosis with ventriculoperitoneal shunt in situ, operated 14 days back was brought to the pediatric emergency with a two-day history of high fever associated with vomiting, irritability, excessive crying, and decreased feeding. Postoperative meningitis was confirmed as cerebrospinal fluid culture revealed P. agglomerans . She responded well with a 14-day intravenous (IV) course of ceftriaxone. Also, we report a case of a 3-year-old male child referred to our center with a provisional diagnosis of UTI with chickenpox for further evaluation. During his 24-hour stay at the local hospital, he had received oral antibiotics and urinary catherization. Urine culture of catheter clamp urine was sterile. P. agglomerans was grown in blood culture. He was treated successfully with IV ceftriaxone and amikacin. Conclusion . P. agglomerans can cause postsurgical meningitis and bloodstream infection in children. The clinical course of infection was mild and timely administration of proper antibiotic resulted in a favorable outcome.